STRATEGI MENINGKATKAN DAYA SAING PADA USAHA KECIL (STUDI KASUS: PRODUKSI KUE TRADISIONAL KAK IRA) - Zaini Novrika; Sumarno Sumarno; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : One type of small business in Kampar regency is Produksi Kue Tradisional Kak Ira needs to be developed to get the opportunity . It is necessary to evaluate the strengths , weaknesses , opportunities and threats that exist in the Produksi Kue Tradisional Kak Ira to take advantage of environmental conditions in the development of its business. The purpose of their research is to determine a strategy to improve competitiveness. Research was conducted on Produksi Kue Tradisional Kak Ira the research object is a strategy to improve the competitiveness of Produksi Kue Tradisional Kak Ira. While the respondents are managers and employees Kue Tradisional Kak Ira. The results of this study indicate that the Produksi Kue Tradisional Kak Ira is in quadrant 14 of the SO strategy , which shows these businesses have environmental opportunities and the many forces that encourage the use of these opportunities. This situation shows the growth -oriented strategy ( growt Oriented Strategy). The study produced alternative strategies that can be used to improve business competitiveness Kue Tradisional Kak Ira include: 1 ) flavors and shapes are more interesting . 2 ) Maintaining the quality of products so that customers remain loyal . 3 ) Expanding market share by opening branches in various regions . 4 ) The product packaging is made more attractive and simple. Keywords : Strategy , Competitiveness , Small Businesses